(untitled) (Research, Society and Development, 2022)
Cleft lip and palate is the most common craniofacial anomaly in humans (1:650 births), and its etiology is multifactorial. Patients with this condition are affected by morphological and functional disorders, including dental malformations, the most common being agenesis, which occurs more frequently in the permanent maxillary lateral incisors on the side where the cleft is located, affecting function, aesthetics and consequently the patient’s self-esteem. The objective of this study was to report the case of a cleft patient with tooth agenesis, to present the alternative used for his rehabilitation and the psychological impact of the treatment. The patient was treated at CEAPAC (Center for Attention and Research in Craniofacial Anomalies) and his main complaint was the agenesis of the upper lateral incisors, the acrylic plate with stock teeth used for rehabilitation and the aesthetics of the upper central incisors that were misaligned and with shape change. The proposed treatment plan was the manufacture of two fixed prostheses, cantilever type, involving the central incisors and the maxillary canines as support for the suspended element, since there was rejection of the graft and the installation of implants was unfeasible. Dental rehabilitation was completed satisfactorily, returning to the patient, within its limitations, not only the function, but also the aesthetics and self-confidence, the patient will continue to be followed up for clinical follow-up of the case. The importance of care by a specialized multidisciplinary team is highlighted, considering the complexity of the anomaly and the need for comprehensive rehabilitation.